Monitoring Pengetahuan Tanya 5O dan Dagusibu Obat yang Benar pada Ibu PKK RT/RW 003/003 Desa Kedanyang, Kebomas, Gresik - Janatun Na’imah; Anindi Lupita Nasyanka; Riskha Aulia (ACADEMICS IN ACTION Journal of Community Empowerment, 2020)
At this time, community does not understand classes of drugs that can be purchase or stored at home. This can have two impacts, positive and negative. The positive impact is community become more responsive to health, while the negative impact is increasing use of drugs which raises problems related to how to get, use, store and dispose of drugs properly or commonly known as Dagusibu. This community service activity aims to educating housewives as "pharmacists" in the household regarding how to get, use, store, and dispose of drugs properly in Kedanyang Village RT/RW 003/003, Kebomas, Gresik. Method that we use in this community service is counseling and training using property and followed with monitoring. We use questionnaire for monitoring a month after counseling and training. Our method to counseling and training involve several variable, including Question of 5”O”, Get, Use, Save and Discard (Dagusibu). The result shows that this activity is effective with the percentage of correct answer for each variable are above 75%, including question about 5”O" as much as 97%, get 84.38%, use 87.14%, save 76%, and waste 93%. This proved that the method chosen in this community service is appropriate, where the community still remember and understand.